Bases tecnológicas da Biblioteconomia e Ciência da Informação no Brasil: análise da tecnologia como assunto de pesquisa e conteúdo na formação - Ronaldo Ferreira de Araujo (2015)
This research aims to contribute to the reflection of the relationship between the Library and Information Science (LIS) with the technological component as identification mark of these areas. Then we investigate scientific research on technological themes and their consonance with technology while educational content in these interdisciplinary fields, trying to answer: what are the technological basis of LIS in Brazil? Technicist, philosophical, cultural and sociological conceptions on the subject constitute the theoretical framework of research on the observation perspectives of different thinkers (Heidegger, Morin, Lévy and Vieira Pinto). The accumulated technological knowledge on Annual Review of Information Science and Technology (ARIST) in the last 50 years complements the theoretical framework and underpins the proposed creation of a selection tool and analyze national scientific production represented on BRAPCI database, for a total of 422 articles. The premise of the relationship between the Library and Information Science for analysis of technology as educational content, the curriculum of technological disciplines of undergraduate courses in Librarianship and the Information Science pos-graduation institutions that offer both teams in the same teaching unit (UFBA, UFMG; UFRGS; UFPB, UNB; UNESP, USP) were the empirical research universe by document analysis techniques. The results show a small group of authors among the most productive in both the analysis of the authorship of articles as references, with a high rate of transient authors; It presents a differentiation emphasis on thematic orientation of articles and disciplines, having featured as information systems in the main cluster of both; and indicates the "development and applications" category with the largest number of articles and disciplines about technology. The majority of the curriculums analyzed reproduced a developmental logic eductional perspective in the use of cognitive-instrumental rationality of a curriculum based on compliance. The segments that form the technological basis of LIS are: informatics; information systems; information society; information and knowledge organization and representation; information products and services; information studies on the web; and the electronic communication.